Peroxymonosulfate activation by tea residue biochar loaded with Fe3O4 for the degradation of tetracycline hydrochloride: performance and reaction mechanism. Issue 30 (22nd May 2021) - Wang, Qirui; Shi, Yixuan; Lv, Shiyi; Liang, Ying; Xiao, Pengfei
Abstract : The prepared tea residue biochar loaded with Fe3 O4 has high-efficiency and environmental potential for activating peroxymonosulfate to degrade tetracycline hydrochloride. Abstract : The recycling of agricultural and food waste is an effective way to reduce resource waste and ameliorate the shortage of natural resources. The treatment of antibiotic wastewater is a current research hotspot. In this study, waste tea residue was used as a raw material to prepare biochar (T-BC) and loaded with Fe3 O4 as a catalyst to activate peroxymonosulfate (PMS) for oxidative degradation of tetracycline hydrochloride (TCH). Analysis techniques such as BET, SEM, XRD, FT-IR, XPS and VSM indicated that the heterogeneous catalyst (Fe3 O4 @T-BC) with good surface properties and magnetic properties was successfully prepared. The results of batch-scale experiments illustrated that when the dose of the Fe3 O4 @T-BC catalyst was 1 g L −1, the concentration of PMS was 1 g L −1, and the initial pH was 7, the degradation rate of TCH with a concentration of 50 mg L −1 reached 97.89% after 60 minutes of reaction. When the initial pH was 11, the degradation rate of TCH reached 99.86%. After the catalyst was recycled four times using an external magnet, the degradation rate of TCH could still reach 71.32%. The data of removal of TCH could be best fitted by a pseudo-first-order model. The analysis of the degradation mechanism through a free radical quenching experiment and EPR analysis, as well as the exploration of TCH intermediate products and reaction paths through the LC-MS method, all confirmed that the Fe3 O4 @T-BC prepared by this method is expected to become a cost-effective and environmentally friendly heterogeneous catalyst for activating persulfate degradation of tetracycline antibiotics.